Molecular xenomonitoring for Wuchereria bancrofti in Culex quinquefasciatus in two districts in Bangladesh supports transmission assessment survey findings. - Seth R Irish; Hasan Mohammad Al-Amin; Heather N Paulin; A S M Sultan Mahmood; Rajaul K Khan; A K M Muraduzzaman; Caitlin M Worrell; Meerjady S Flora; Mohammed J Karim; Tahmina Shirin; A K M Shamsuzzaman; Sanya Tahmina; et al. (PLoS Neglected Tropical Diseases, 2018)
Background Careful monitoring for recrudescence of Wuchereria bancrofti infection is necessary in communities where mass drug administration (MDA) for the elimination of lymphatic filariasis (LF) as a public health problem has been stopped. During the post-MDA period, transmission assessment surveys (TAS) are recommended by the World Health Organization to monitor the presence of the parasite in humans. Molecular xenomonitoring (MX), a method by which parasite infection in the mosquito population is monitored, has also been proposed as a sensitive method to determine whether the parasite is still present in the human population. The aim of this study was to conduct an MX evaluation in two areas of Bangladesh, one previously endemic district that had stopped MDA (Panchagarh), and part of a non-endemic district (Gaibandha) that borders the district where transmission was most recently recorded. Methodology/principal findings Mosquitoes were systematically collected from 180 trap sites per district and mosquito pools were tested for W. bancrofti using real-time PCR. A total of 23,436 intact mosquitoes, representing 31 species, were collected from the two districts, of which 10,344 (41%) were Culex quinquefasciatus, the vector of W. bancrofti in Bangladesh. All of the 594 pools of Cx. quinquefasciatus tested by real-time PCR were negative for the presence of W. bancrofti DNA. Conclusions/significance This study suggested the absence of W. bancrofti in these districts. MX could be a sensitive tool to confirm interruption of LF transmission in areas considered at higher risk of recrudescence, particularly in countries like Bangladesh where entomological and laboratory capacity to perform MX is available.